Deficiency in NPC2 results in disruption of mitochondria-late endosome/lysosomes contact sites and endo-lysosomal lipid dyshomeostasis - Raffaele Pastore; Lihang Yao; Nathan Hatcher; Martin Helley; Janet Brownlees; Radha Desai (Scientific Reports)
Abstract Dysfunction of the endo-lysosomal intracellular Cholesterol transporter 2 protein (NPC2) leads to the onset of Niemann–Pick Disease Type C (NPC), a lysosomal storage disorder. Metabolic and homeostatic mechanisms are disrupted in lysosomal storage disorders (LSDs) hence we characterized a cellular model of NPC2 knock out, to assess alterations in organellar function and inter-organellar crosstalk between mitochondria and lysosomes. We performed characterization of lipid alterations and confirmed altered lysosomal morphology, but no overt changes in oxidative stress markers. Using several techniques, we demonstrated that contacts between mitochondria and late endosomes/lysosomes are reduced in NPC2−/− HEK cells, we observed that the acidic compartments are swollen and lipid dense. Quantification of endogenous lipids in HEKNPC2−/− cells by mass spectrometry reveals accumulation of lipid species indicative of sphingolipid metabolic dysregulation within the lysosome. Specifically, HEK NPC2−/− cells exhibit marked elevation of glucosylsphingosine and glucosylceramides, substrates of beta glucocerebroside (GBA), as well as accumulation of sphingosine and sphingomyelins. Our studies suggest an involvement of NPC2 in the formation of contact sites between mitochondria and lysosomes and support the hypothesis of a role for NPC2 in the endo-lysosomal trafficking pathway and dynamic organellar crosstalk.